[PP.26.06] DO DRUGS INTERACT TOGETHER IN CARDIOVASCULAR PREVENTION? A META-ANALYSIS OF POWERFUL OF FACTORIAL RANDOMIZE CONTROLLED TRIALS. (September 2016) - Fall, M.; Le, H.; Al-Gobari, M.; Grenet, G.; Cucherat, M.; Dieye, A.; Gueyffier, F.
Abstract : Objective: Four major drugs classes (antihypertensive drugs, antiplatelet agents, lipid lowering drugs or antidiabetic agents) prevent efficiently cardiovascular diseases. They are frequently combined for the patient's treatment. Whether these treatments interact together on was never evaluated. We explored interactions between drugs in terms of cardiovascular risks reduction. Design and method: We analyzed powerful randomized controlled trials included in previous meta-analyses and presenting results according to co-prescriptions, published up to November 2015 and assessing one of the four major drug classes. We explored the changes of the drug effects according to the cross-exposure to other drug classes. When unavailable, other classes drugs exposure was assimilated to the risk factor as hypertension or diabetes. Comparisons of Major Coronary Event or Major Vascular Event between treatment sub-groups were expressed by the pooled Relative Risks (RRs) with 95% Confidence Intervals (CIs). We explored heterogeneity between co-prescription subgroups to measure the interaction. We took p > 0.10 and I 2 > 50% to consider a significant interaction. When no interaction was observed, we illustrated to what extent potentially significant interaction could be eliminated, through analyzing RRs ratio with their 95% CIs. Results: Eighteen trials with a total of 164 947 intention to-treat participants were analyzed with an average duration of follow-up of 3.6 years. The relative risks associated with these treatments ranged from 0.72 [0.69–0.76] to 0.80 [0.76–0.84], all were statistically significant. We did not observe any interaction with co-prescription, diabetes or hypertensive status. The lack of significant interaction did not eliminate all possibility of such treatment modification. However, our results allowed eliminating treatment changes above 50 % of the relative benefit for all interactions, and above 20% for the benefit of statin according to hypertension. Conclusions: We observed a lack of significant interaction between the impact of statins, antihypertensive drugs, antidiabetic drugs and aspirin on hypertension or diabetes status on one hand, and their co-prescription on the other hand. We could eliminate treatment changes in relative benefit terms above 50%.